The Spirit of Nationalism in Literature: A Case Study of Students in Yogyakarta - Anang Sudigdo; Onok Yayang Pamungkas; Hastangka; Sabar Budi Raharjo; Suprapto (Indonesia Approach Education, 2023)
This research is an effort to investigate the understanding of prospective student teachers in the PGSD Study Program at